Reverse osmosis desalination in a mini renewable energy power supply system - Zhao, Yu (Curtin University, 2006)
The design, construction and testing of a reverse-osmosis (PV-RO) desalination system for fresh water shortage area is presented. The system operates from salt water or brackish water and can be embedded in a renewable energy power supply system, since many fresh shortage areas are remote and isolated. Special attention is given to the energy efficiency of small-scale reverse osmosis desalination systems. Limitations of conventional control strategy using toggle control are presented. Based on this, an objective of creating a small-scale reverse osmosis desalination system was set out. Initially, the background information is presented. This includes the natural resources crisis and main desalination technologies and the viability of the integration with renewable energy source. A reverse osmosis (RO) desalination system was assembled and set up at the Curtin University of Technology, Perth, Western Australia Supervisor Control And Data Acquisition (SCADA) system was built using a Human Machine Interface software and a programmable logic controller (PLC). Instrumentation that included signal conditioners was made in analysis of the system characteristics. Initial testing of the system was conducted after the system design and configuration was accomplished. Testing results were used as a guideline for the development of the whole system.Modelling and simulation of the system components in MATLABSimulink is presented, together with a discussion of the control systems modelling and design procedure, in which the aim was to improve the efficiency of the reverse osmosis system. Simulations show the designed reverse osmosis system with Proportional Integral and Derivative (PID) controller has better performance than other controllers. This consequently leads to a lower overall cost of the water, as well as reducing full maintenance cost of the electric drives in the reverse osmosis unit. Additionally, the configuration of the remote control system through General Package Radio System (GPRS) network is depicted. After the PID control algorithm was programmed into the Programmable Logic Controller (PLC), system experiments were carried out in short durations and long durations. System performance was monitored and experimental results prove that the new control strategy applied increase the water productivity and is able to improve the system efficiency up to 35%. Based on the data obtained from the simulations and experiments, Mundoo Island was chosen to be the location for a case study. The electric load profile of the island was derived from the Island Development Committee in Mundoo.A water demand profile was created and modelled in Matlab to be the input of the reverse osmosis system. The electric load of the reverse osmosis system was generated from Matlab simulation. This result was entered in Hybrid Optimisation Model for Electric Renewables (HOMER) simulator. Having the designed RO unit as one of the electric loads, the entire remote area power supply (RAPS) system was tested in simulations which shows the energy cost is AUS$0.174 per kWh, lower than the Island Development Committee budget estimation of AUS$0.25 per kWh. The cost of the water treatment is very promising at AUS$0.77 per m3.